Modeling Hydrogen-Bonding in Diblock Copolymer/Homopolymer Blends - Dehghan, Kooshkghazi Ashkan (My University, 2012)
The phase behavior of AB diblock copolymers mixed with C homopolymers (AB/C), in which A and C are capable of forming hydrogen-bonds, is examined using self-consistent ﬁeld theory. The study focuses on the modeling of hydrogen-bonding in polymers. Speciﬁcally, we examine two models for the formation of hydrogen-bonds between polymer chains. The ﬁrst commonly used model assumes a large attractive interaction parameter between the A/C monomers. This model reproduces correct phase transition sequences as compared with experiments, but it fails to correctly describe the change of lamellar spacing induced by the addition of the C homopolymers. The second model is based on the fact that hydrogen-bonding leads to A/C complexation. We show that the interpolymer complexation model predicts correctly the order-order phase transition sequences and the decrease of lamellar spacing for strong hydrogen-bonding. Our analysis demonstrates that hydrogen-bonding of polymers should be modeled by interpolymer complexation.
Keywords: SCFT; Diblock Copolymer; Homopolymer; Hydrogen Bonding; Self-Consistent Field Theory; Phase transitions; Biological and Chemical Physics; Condensed Matter Physics; Statistical Models; Biological and Chemical Physics